Penerapan Model Pembelajaran IKRAR untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas X Tata Boga SMK Nusa Dua Sawan Tahun Ajaran 2012/2013 - Kadek Evi Wellyastini; I Gede Sudirta; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study was aimed to (1) know the student’s learning activity result of X.TB class at SMK Nusa Dua Sawan in 2012/2013 of Computer skill and information processing (CSIP), (2) know the student’s learning result of computer skill and information processing (CSIP) lesson using IKRAR learning model; (3) know the student’s  response of X.TB class to apply the IKRAR model of computer skill and information processing (CSIP). This study is a classroom action research design that used  by involving a total Number of 30 students of X.AP class at SMK Nusa Dua Sawan first semester in 2012/2013. The object of this research  emphasized on the students activity, result and students response in basic competency to operated text principle sistem of computer skill and information processing (CSIP). The learning students  result data was collected based on cognitive test and affective observation. Meanwhile,the  student’s response and activity data was collected by using questionnaire. The obtained data were analyzed descriptively. The result of the study showed that (1) there was improvement of learning student’s result of  X.TB class at II cycle to apply the IKRAR model of computer skill and information processing (CSIP). the results indicated that the learning students result score include: averaging class, and classical completeness learning students was improvement (2) there is improvement of learning activity students’ by apply the IKRAR learning (3) the students’ responses towards IKRAR model of computer skill and information processing (CSIP) is really positive.